Condiciones que presenta la sopa teóloga y el shámbar para el turismo gastronómico en la provincia de Trujillo. - Horna Obregón, Fiorella Maritza (2019)
The present research work was oriented to determine the conditions that the typical dishes present: the theologian soup and the shámbar for the practice of gastronomic tourism in the province of Trujillo, addressing the potential existing gastronomy of these typical dishes, allowing to demonstrate that according to the trends regarding gastronomy are offering these dishes but it is necessary to strengthen their dissemination._x000D_ Today, this topic has been prioritized in the tourist offer both nationally and internationally, because there is a tourist flow looking for this type of attraction, since the trend is oriented towards a healthy diet and that nourishes properly, that is why This study has been eveloped taking into account the inputs of the area used in the preparation of these typical dishes, recipes, procedures and techniques of preparation, as well as restaurants willing to present the dishes on the menu. For which we proceeded to apply the inductive-deductive, analytical-synthetic and ethnographic method that were useful in the cabinet stage and in the field stage, also the means to develop these methods were direct observation, photographic record, notebook of field and guide of applied interviews the suppliers of inputs, the native cooks and the representatives of the categorized restaurants that fulfilled the profile of study._x000D_ Checking the general hypothesis, concluding that the inputs, procedures and techniques used in these typical dishes have been preserved until today and offered in the main restaurants in the province of Trujillo, making it possible to include these typical dishes